Comparative Study of FAWAG and SWAG as an Effective EOR Technique for a Malaysian Field. - Tunio, Saleem Qadir (Maxwell Scientific Organization, 2012)
At present, petroleum engineering has become economics based field hence all efforts are taken to make sure that we squeeze out the last drop of oil from the reservoir. Field “A”, one of Malaysian oil field is a strong candidate for Enhanced Oil Recovery (EOR) which was producing for more than 15 years. Currently Simultaneous Water Alternating Gas (SWAG) along with other techniques tends to improve oil recovery by improving reservoir fluids mobility and providing driving force. Foam can also be added in water alternating gas technique to improve the sweeping mechanism and cut off the gas production which is termed as Foam Assisted Water-Alternating Gas (FAWAG). In this study, a comparison has been made between FAWAG and SWAG in order to come up with the effective method of EOR for a better oil recovery. Core flood experiments have been carried out for evaluating both techniques. Mathematical modeling of FAWAG and SWAG are not included in this comparative study. Experimental results shows that, SWAG tends to address all recovery related problems economically where as foam has been seen to address the problems by assisting other Enhanced Oil Recovery Techniques and proved that foam assistance has given better recovery.